Wärmemangel- und Trockengrenzen der Vegetation in ihrer Beziehung zu den Luftmassengrenzen - Klaus, Dieter (ERDKUNDE, 1979)
The median position of frontal zones as well as of important limits of air masses for winter- and summer months is defined by the counting of the frequency of meteorological frontal zones during the period 1949-1978.The limits of the air masses show a good spatial coincidence with significant borderlines of the macro-regional natural order of the vegetation. Historically proven changes in the course taken by limits of vegetation zones can provide indirect information about changes in the position of the frontal zones and thus about variations of the atmospheric structure of circulation by way of these correlations between air mass boundaries and vegetation.